PENGARUH KOMPENSASI, MOTIVASI, KEPUASAN KERJA TERHADAP LOYALITAS PEKERJA - Diskon Sitinjak; Yossi Hendriati; Indra Firdiyansyah (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This study was conducted through surveys or distributing questionnaires to 40 employees of the Batam Fygaleri store. The technique of collecting data is through distributing questionnaires and testing its validity and reliability. . Technique The data analysis used to answer the research hypothesis is the test regression, Classical Assumptions. The results showed Compensation variable (X1) has a significant effect on Employee Loyalty in Batam Fygaleri Stores. It can be seen that t count is 2.256 > t table 1.683, and Sig 0.000 < 0.05, which means that compensation has a role in influencing the Loyalty of Workers in Batam Fygaleri Stores, Motivation variable (X2) has a significant influence on the Loyalty of Workers in Batam Fygaleri Stores. It can be seen that t count is 2.158 > t table 1.683, and Sig 0.001 < 0.05, which means that motivation has a role in Employee Loyalty at Batam Fygaleri Stores, Work variables (X3) have a significant effect on Employee Loyalty in Batam Fygaleri Stores. It can be seen that t count 5.406 > t table 1.683, and Sig 0.000 < 0.05, which means that work has a role in influencing Employee Loyalty at Batam Fygaleri Stores, Variables Compensation, Motivation, the purpose of working together have a significant influence on the Loyalty of Workers in Batam Fygaleri Stores. It can be seen that f count (14,193) > f table (2.84) which shows that compensation, motivation, work goals have a role in influencing employee loyalty at the Batam Fygaleri Store